Synthetic enamine naphthoquinone derived from lawsone as cytotoxic agents assessed by in vitro and in silico evaluations. (1st December 2021) - Lemos, Bárbara C.; Westphal, Regina; Filho, Eclair Venturini; Fiorot, Rodolfo G.; Carneiro, José Walkimar M.; Gomes, Anne Caroline C.; Guimarães, Celina J.; de Oliveira, Fátima C.E.; Costa, Pedro Mikael S.; Pessoa, Claudia; Greco, Sandro J.
Graphical abstract: Highlights: Ten enamine naphthoquinones were satisfactorily synthesized. The antiproliferative activity were determined in four human cancer line cell. Qualitative Structure/Biological Activity relationship was made. Docking indicated that molecules inhibit topoisomerase and thymidylate synthase. Abstract: We synthesized ten enamine naphthoquinones with yields ranging from 43 to 76%. These compounds were screened for their in vitro antiproliferative activities by MTT assay against four types of human cancer cell lines: HCT116, PC3, HL60 and SNB19. The naphthoquinones bearing the picolylamine (7 ) and quinoline (12 ) moieties were the most actives (IC50  < 24 μM for all the cell lines), which were comparable or better to the values obtained for the control drugs. In silico evaluations allowed us to develop a qualitative Structure-Activity Relationship which suggest that electrostatic features, particularly the C 2 –C3 internuclear repulsion and the molecular dipole moment, relate to the biological response. Furthermore, Molecular Docking simulations indicate that the synthetic compounds have the potential to act as anticancer molecules by inhibiting topoisomerase-II and thymidylate synthase.